Understanding Lessons Of Ethics In The Primary Education Of Bangladesh - Kabir, Alamgir; Imam, Mehedi (Bangladesh Journal of Bioethics, 2012)
In a bid to understand the lesson of ethics in the existing primary education according to government approved syllabus in Bangladesh, a survey was carried out in Dhaka and Kushtia for students studying at class 1 to class V, teachers and guardians. It has found that majority students are aware of ‘right and wrong’. Their source of learning are parents as mostly found, followed by teachers and both. Majority of guardians think text books contain ethical knowledge and they are insufficient. All the teachers found the textbooks contain ethical knowledge and education but only one forth of them found those as insufficient. On appropriateness of the lessons, only a few teachers were satisfied but majority felt the need of ethical knowledge according to age and psychology. In the text books, moral lessons are found in religion, social and environmental context as a mere advice. They are available in the form of do’s and don’ts. Stories carry ethical lesson but no individual lesson/chapter was found to be available in any books. The paper has tried to understand the existing syllabus in government run primary schools up to class V through interviewing students, teachers and guardians so that the level of lessons taught, and the need to learn the ethical knowledge can be assessed. DOI: http://dx.doi.org/10.3329/bioethics.v1i3.9634 Bangladesh Journal of Bioethics 2010; 1(3): 47-51